Capital intelectual em empresas de TI: perfil e mensuração de valor em prestadores de serviço no Estado do Rio de Janeiro - Gomes, Bruno Cezar Pinto Aderne (2014)
This research studied the determinants of Intellectual Capital Management in companies providing services in Information Technology in the state of Rio de Janeiro. Were surveyed the Importance, the Measurability and the Implementation perceptions of the components of the Intellectual Capital and of the Financial Capital. From the data analysis, it was possible to segregate companies into three hierarchical clusters, oriented to each of its capacities. It was also possible to perform correlations on the constructs of Intellectual Capital and Financial Capital. Contributing to the ICT sector, this study may help future managers, or companies that operate facing deficiencies, to see more effectively the constructs and variables of Intellectual Capital and Financial Capital in the value creation adjustments, and carry on their businesses in search maximizing the results. It was demonstrated that subjects recognized the importance of intellectual capital to generate different levels of value. One of the groups of respondents acknowledged as being the most important for value creation the Human Capital and the Relationship Capital; another pointed out the importance of Financial Capital and Organizational Capital in generating value for the business, leading to heterogeneity business profiles.